Recuperação de componentes de metal duro por projeção térmica - Rodrigues, Fábio Wilson Pinto (2018)
The main objective of this work is the development of a hardmetal components (WC-6%Co) recovery method by thermal deposition process. The thermal deposition technique used was HVOF (high velocity oxygen-fuel). The HVOF enables depositions of thick coatings (100-500 µm) with low porosity levels, high hardness and excellent adhesion. Before deposition, hardmetal samples with different geometries (plates and cylinders) were finished in order to have different roughness. The influence of these parameters in adhesion was studied. After this step, different re-sintering temperatures were used, in order to determine which one allows to obtain the maxima densification, elements distribution and metallurgical bonding. The re-sintering promotes the densification of the coating, with an increase of its hardness and metallurgical bonding formation. The inclusion of an intermetallic layer was tested along with different layer parameters. In liquid phase sintering (1383 and 1455 ºC) a complete densification of the coating occurred, while a bonding between the substrate and the coating only partially happened. The results of SEM/EDS show low levels of porosity and a complete and uniform distribution of the elements of the alloy. The cylindrical samples without intermetallic layer showed the lowest level of porosity and best metallurgical bonding. When the substrate surface was polished (Ra = 0.05 mm) lower levels of porosity and greater metallurgical bonding were found for both geometries. Taking into account the results obtained in this study, we can conclude that the implementation of this process is appropriate for cylindrical components with a polished surface. In these components the intermetallic layer is unnecessary and punctual defects like pores can be repaired with this process.